The Role of Emerging Technologies in Improving Academic Advising System Study: An Applied Study for the Faculty of Information Technology at Alasmarya Islamic University - عجالة, حياة; Al-Haram, Souad; Baij, Aisha (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Emerging technologies are new technologies that are in the process of being used or tested and play an important role in accelerating the pace of educational transformation. Emerging modern technologies have been employed to improve the role of academic advising in higher education institutions, and academic advising is considered a crucial factor in student success. It enhances student engagement with the institution by providing support to students in their academic progress and career goals. The motivation behind this research is to pave the way for effective utilization of the available opportunities offered by these technologies. Most traditional academic advising systems lack support for multiple new data sources and real-time big data processing tools that can aid in decision-making with fast and accurate results. This study dealt with a review of previous literature on some of the techniques that have been used to improve the role of academic advising, and as an applied aspect it is part of a major research aimed at transferring traditional academic advising to a web-based one for the Faculty of Information Technology at Alasmarya Islamic University; Considering that web application technology is one of the emerging technologies that is widespread at the present and plays a role in improving job performance in educational institutions. The primary sources that were relied upon to collect data took the descriptive approach to review previous studies, and among the programs and languages ​​used in designing this system (website) was the Visual Studio Code program, and the interfaces in it were designed using the HTML design language, the PHP programming language, and the CSS formatting language. One of the most important results of the study is the effectiveness of using web applications. A website was designed to facilitate use and address the problems faced by students, linking the academic advisor with his students and facilitating means of communication between them. We also enumerate some important cases of emerging technologies in use. Finally, we highlight the most important research challenges that must be addressed in such an important field of research.
Keywords: Emerging technologies; Data mining; Artificial intelligence; Applications (smart phone/ web); Academic advising